Overview of immunosuppression in liver transplantation - Pillai, Anjana A (The WJG Press and Baishideng, 2009)
Continued advances in surgical techniques and immunosuppressive therapy have allowed liver transplantation to become an extremely successful treatment option for patients with end-stage liver disease. Beginning with the revolutionary discovery of cyclosporine in the 1970s, immunosuppressive regimens have evolved greatly and current statistics confirm one-year graft survival rates in excess of 80%. Immunosuppressive regimens include calcineurin inhibitors, anti-metabolites, mTOR inhibitors, steroids and antibody-based therapies. These agents target different sites in the T cell activation cascade, usually by inhibiting T cell activation or via T cell depletion. They are used as induction therapy in the immediate peri- and post-operative period, as long-term maintenance medications to preserve graft function and as salvage therapy for acute rejection in liver transplant recipients. This review will focus on existing immunosuppressive agents for liver transplantation and consider newer medications on the horizon.